CONSUMER PROTECTION AGAINST HALAL-LABELED MARSHMALLOW PRODUCTS CONTAINING PORK INGREDIENTS FROM THE PERSPECTIVE OF LAW NO. 33 OF 2014 CONCERNING HALAL PRODUCT GUARANTEES - Irma Yani Siagian; Sudirman Suparmin (Journal Analytica Islamica, 2025)
Halal products are essential for Indonesian Muslims as a form of protection and consumption in accordance with sharia. However, public trust in the halal label was shaken after the BPJPH (Indonesian Food and Drug Authority) and the BPOM (Indonesian Food and Drug Authority) discovered nine halal-labeled marshmallow products that contained pork in early 2025. This study aims to analyze the legal protection provided to consumers for products that do not comply with the halal label, specifically from the perspective of Law No. 33 of 2014 concerning Halal Product Assurance. This study uses a normative juridical method with a statutory, conceptual, and case-based approach. The results show that businesses that illegally use the halal label can be subject to criminal and administrative sanctions in accordance with statutory provisions. On the other hand, consumers have the right to legal protection, both materially and spiritually. To address this issue, strengthening the monitoring system, digital transparency, consumer and business education, and strict law enforcement against violations of the halal label are needed. This research is expected to strengthen the halal product assurance system and increase legal awareness of all parties involved.